2021
DOI: 10.1146/annurev-financial-100620-065648
|View full text |Cite
|
Sign up to set email alerts
|

Does the Yield Curve Predict Output?

Abstract: Does the yield curve have the ability to predict output and recessions? At some times and in certain places, of course! But when and where, which aspects of the curve matter most, and which economic forces account for the predictive ability are matters of dispute. Over the years, an increasingly sophisticated set of tools, both statistical and theoretical, has addressed the issue. For the United States, an inverted yield curve, particularly when the spread between the yield on 10-year and 3-month Treasuries be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 96 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…In turn, considering low rate periods is related to the question of how monetary regimes affect the predictive ability of the yield curve: Bordo and Haubrich (2008a,b) have suggested that the monetary regime may play a role, Giacomini and Rossi (2006) provide evidence that changes in monetary policy have led to breakdowns in predictive accuracy, and Benati and Goodhart (2008) show that changing inflation persistence matters, a finding that has extensive overlap with the first question, as short rates are often used as an indicator of monetary policy. These are all part of the rich literature that documents and explains the predictive ability of the yield curve; see the surveys by Estrella (2005), Wheelock and Wohar (2009) and Haubrich (2021). As such it also contributes to understanding the economics of low interest rate environments, as in Ramey and Zubairy (2018), Sims and Wu (2020), and Eggertsson and Woodford (2003).…”
Section: Introductionmentioning
confidence: 94%
“…In turn, considering low rate periods is related to the question of how monetary regimes affect the predictive ability of the yield curve: Bordo and Haubrich (2008a,b) have suggested that the monetary regime may play a role, Giacomini and Rossi (2006) provide evidence that changes in monetary policy have led to breakdowns in predictive accuracy, and Benati and Goodhart (2008) show that changing inflation persistence matters, a finding that has extensive overlap with the first question, as short rates are often used as an indicator of monetary policy. These are all part of the rich literature that documents and explains the predictive ability of the yield curve; see the surveys by Estrella (2005), Wheelock and Wohar (2009) and Haubrich (2021). As such it also contributes to understanding the economics of low interest rate environments, as in Ramey and Zubairy (2018), Sims and Wu (2020), and Eggertsson and Woodford (2003).…”
Section: Introductionmentioning
confidence: 94%